2003
DOI: 10.1207/s15327914nc4702_5
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss During Radiotherapy for Head and Neck Malignancies: What Factors Impact It?

Abstract: Radiotherapy (RT) is an important treatment modality in head and neck cancers. Loss of weight during RT due to various factors is a matter of concern. This study was conducted to see the pattern of weight loss and the causative factors involved. One hundred forty patients with head and neck cancer treated with radical RT, concurrent chemoradiation, or postoperative RT were retrospectively studied. A dose of 70 Gy was given in the radical and in the chemoradiation schedule. In postoperative RT, a dose of 60-64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 14 publications
4
56
1
2
Order By: Relevance
“…In a retrospective study involving 140 HN cancer patients, Munshi et al found that a pretreatment KPS >80 was associated with lower weight loss during RT. 21 Only the pretreatment weight was positively and linearly associated with weight loss in our study. When body mass index (weight/height 2 ) was considered in the final model instead of baseline body weight, similar results were observed (data not shown).…”
Section: Weight Loss In Head Andcontrasting
confidence: 43%
See 3 more Smart Citations
“…In a retrospective study involving 140 HN cancer patients, Munshi et al found that a pretreatment KPS >80 was associated with lower weight loss during RT. 21 Only the pretreatment weight was positively and linearly associated with weight loss in our study. When body mass index (weight/height 2 ) was considered in the final model instead of baseline body weight, similar results were observed (data not shown).…”
Section: Weight Loss In Head Andcontrasting
confidence: 43%
“…Literature data suggest that this percentage is probably underestimated, because weight loss is already observed before diagnosis and can continue after treatment. 5,6,8,14,21,43 Jager-Wittenaar et al report that 19% of the HN cancer patients, all stages combined, had experienced critical weight loss before treatment. 6 In a study of 249 all-stage HN cancer patients, Beaver et al found those who had lost >7% of their body mass index before their cancer treatment had a significantly higher incidence of severe weight loss during RT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study in this area is required to understand causal relationships and potential corrective interventions, whether they be nutritional, or psychological. Munshi et al 26 Poor performance status, chemoradiotherapy and doses >60…”
Section: Patient Characteristicsmentioning
confidence: 99%